ASNS can predict the poor prognosis of clear cell renal cell carcinoma - Gan, Xinqiang; Liu, Ruiji; Cheng, Hong; Mao, Weipu; Feng, Ninghan; Chen, Ming (Frontiers in Oncology, 2022)
Purpose: Clear cell renal cell carcinoma (ccRCC) is one of the most common malignancies of the urinary system. This study was conducted to discover a new target that can predict the prognosis and promote the treatment of ccRCC. Methods: The raw data were downloaded from the TCGA database, and the predictive value of ASNS for various clinicopathological features was verified in the following analysis. Then we analyzed the potential involvement of ASNS in tumor immunity and obtained the possible pathways involving ASNS through GO/KEGG enrichment analysis and GSEA. We also further verified our findings in pathological specimens of ccRCC patients. Results: ASNS expression was significantly increased in ccRCC, which was associated with advanced clinicopathological characteristics. It was an independent prognostic factor for overall survival in 535 patients with ccRCC. Immune cell infiltration analysis revealed that ASNS expression was related to T lymphocyte infiltration of tumors and poor prognosis. Moreover, we performed relevant functional enrichment analyses of ASNS. Conclusions: ASNS might play a significant role in the development and immune cell infiltration of ccRCC and serve as a valuable clinical prognostic biomarker.